2017
DOI: 10.1007/s41062-017-0098-z
|View full text |Cite
|
Sign up to set email alerts
|

A convergence criterion for water conveyance tunnels

Abstract: One of the important methods used by tunnel construction engineers to examine the design, construction safety factor, and tunnel boring procedures is convergence measurement. Larger convergences may lead to safety problems such as rock destruction, boring machines jamming, delays in projects, or even geological disasters, in which case convergence measurement is considered the best method. The goal of this research is introducing a new convergence criterion for water conveyance tunnel based on the data from 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It is concluded that the accuracy of the MARS method is lower than that of the MLP model. Zarei et al utilized SPSS and discrete element methods to introduce a new convergence criterion for water conveyance tunnel, and it comes out that the ANN is more suitable than the other two methods [69]. Note that the performance of different data mining methods and statistical methods varies depending on different data.…”
Section: F Tunnel Convergencementioning
confidence: 99%
See 1 more Smart Citation
“…It is concluded that the accuracy of the MARS method is lower than that of the MLP model. Zarei et al utilized SPSS and discrete element methods to introduce a new convergence criterion for water conveyance tunnel, and it comes out that the ANN is more suitable than the other two methods [69]. Note that the performance of different data mining methods and statistical methods varies depending on different data.…”
Section: F Tunnel Convergencementioning
confidence: 99%
“…Nevertheless, the abovementioned conclusions can provide a reference in the tunnel engineering field. [21] WNN>ANN [22] GP>SVM>ANN [78] SVMFF>ANNFF [79] MLP>MRA [76] PSO-ANN>ANN [93] ANFIS>CFT>ANN [5] FLM>BPNN>MRA [20] ICA-ANN>ANN>LMRA [94] TL>RNN>SVM [49] PSO-SVR>PSO-BPNN>PSO-ELM [53] Stability BPNN>LRM [56] MLP>RBFNN [58] TBM performance BPNN>NMRA [59] ANN>SPSS [31] ANN>MRA [60] ANN>LMRA [30] ICA-ANN>PSO-ANN>ANN [61] SVM>ANN [39] PSO-ANN>ICA-ANN>ANN [24] Geological conditions ANN>XGBoost, CatBoost, RF, DT, SVR, KNN, BLR [18] Overbreak ANN>NMRA>LMRA [67] ANFIS>FLM>ANN>SVM>NMRA>L MRA [38] GA-ANN>ANN [68] ABC-ANN>ANN [40] ABC-ANN>ANN [11] Tunnel convergence MLP>RBFNN>MRA [36] SVM>ANN [35] MLP>MARS [69] MLP>SPSS [70] Rockburst and flying rocks PSO-ANN>ICA-ANN>GA-ANN Note: The '>' means the performance of the left model outperforms the right one.…”
Section: A Characteristics Of Ann-based Modelsmentioning
confidence: 99%